Table of Content - - (Journal of agricultural, environmental and veterinary sciences, 2024)
Table of Content:1. Effect of humic supplementation on the germination rate and some morphological characters of three cultivars of sorghum under salt stress conditionsDr. Ghada Mohammed Rashid Al-Taha2. The Effect of Climate Elements Represented by Temperature, Wind Speed, Relative Humidity and Precipitation on the Production of Organic Barley Harvest  in the Kingdom of BahrainMs. Huda Fadhalalla Galadari3. The Forest Heritage of Rosemary in the Taourirt Region - Eastern Morocco - Between Smuggling and UprootingDr. Mohammed Lakhdari,Dr. Jaouad El-Bazoui,Dr. Mohamed Aziach, Dr. Abdelouahed Bouberria4. Evaluating the efficiency of some safe management methods for root-knot nematodes on eggplant in compare with a nematicide, VaydateMr. Hafiz Mohamed Dafalla Yousif, Prof. Fahad Abdullah Al-Yahya, Mr. Mostafa Ahmed El-Qurashi5. Analysis of Al Haydawan (Boerhavia elegana) Seed Extracts: Mineral Composition, Total Phenolic Content, and Primary Antioxidant ActivityMs. Suad Ali Sulaiman Almegairshah, Dr. Asmahan Azhari Ali, Prof. Sahar Hassan Salah Mohamed6. Compensatory growth in Nubian female goats in Sudan Effect on performance (A)Co-Prof. Yagoub Magboul Yagoub, Prof. Salih Ahmed Babiker
Keywords: Journal of Agricultural, Environmental and Veterinary Sciences